Association of BMI with erectile dysfunction: A cross-sectional study of men from an andrology clinic - Liu, Yixun; Hu, Xuechun; Xiong, Mengneng; Li, Jiyan; Jiang, Xiaohua; Wan, Yangyang; Bai, Shun; Zhang, Xiansheng (Frontiers in Endocrinology, 2023)
Abnormal body mass index (BMI) is associated with an increased risk of erectile dysfunction (ED). However, the relationship between different BMI categories and the levels of ED severity remains unclear. In the current study, 878 men from the andrology clinic in Central China were recruited. Erectile function was assessed by the International Index of Erectile Function (IIEF) scores. Questionnaires included questions about demographic characteristics (age, height, weight, educational status), lifestyle habits (drinking, smoking, sleep time), and medical history. Logistic regression was used to examine the association between ED risk and BMI. The incidence of ED was 53.1%. BMI was significantly higher in men from the ED group than in those from the non-ED group (P = 0.01). Compared with the normal weight group, obese men had a higher risk of ED (OR = 1.97, 95% CI = 1.25-3.14, P = 0.004), even after adjustment for potential confounders (OR = 1.78, 95% CI = 1.10-2.90, P = 0.02). Moreover, the positive correlation between obesity and moderate/severe ED severity was confirmed by logistic regression analysis (moderate/severe ED, OR = 2.71, 95% CI = 1.44-5.04, P = 0.002), even after adjusting for potential confounders (OR = 2.51 95% CI = 1.24-5.09, P = 0.01). Collectively, our findings indicate a positive correlation between obesity and the risk of moderate/severe ED. Clinicians could pay more attention to moderate/severe ED patients to maintain a healthy body weight to improve erectile function.